FENOMOLOGI AMEL YANG MEMAINKAN PERAN SEBAGAI WARIA HETEROSEKSUAL DI KOTA BANDUNG - Vikri Adha Rismawan; Lusiawati, Ira (KOMUNIKA BANGSA, 2025)
Gender and sexuality are interesting and very important object of research because it has its own challenges in the social, normative, cultural and religious contexts in Indonesia. One gender expression that often becomes a topic of conversation in society is transwoman. Waria stands for Wanita Pria where men who are and behave, look, and speak like women. The purpose of this study is to identify the experiences, feelings, and meanings of Amel who plays the role of a heterosexual transvestite in Bandung City. A descriptive qualitative approach was used because this research focuses on an in-depth understanding of the subjective experience of a heterosexual waria. By basing on the phenomenological approach developed by Edmund Husserl as the main theory and Alfred Schutz as the supporting theory. This study reveals that Amel's life experiences, feelings, and meanings are the result of constructions that occur through interactions between her subjective awareness, her environment, and the social network that surrounds her